HUMOROUS CONVERSATION ANALYSIS BETWEEN SHERLOCK HOLMES AND DR. WATSON IN SHERLOCK HOLMES “A GAME OF SHADOWS” MOVIE - MAFISAWATI, EKA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key Words: Humor, Solidarity-based function, Power-based function, Sherlock Holmes: a Game of Shadows Humor has always been an important part of human life since it becomes one of strategies that helps people to deliver their intended message in communication process. It serves various functions which can be classified into two broad terms. First, solidarity-based function is a way to use humor in attempt to establish and maintain social cohesion. Second function is power-based function which concerns in using humor as a strategy to disguise unacceptable messages. Humor can also be encountered in movies. The researcher conducted a research on conversational humor in Sherlock Holmes: a Game of Shadows movie. There are two proposed problems: (1) What types of humor are used in conversation between Sherlock Holmes and Dr. Watson in Sherlock Holmes: a Games of Shadow movie, and (2) What are the functions of humor used in conversation between Sherlock Holmes and Dr. Watson in Sherlock Holmes: a Games of Shadow movie. To answer the problems of study the researcher applied two theories namely theory of type of conversational humor by Dynel (2009) to answer the first problem and theory of function of conversational humor by Holmes (1998) to answer the second problem.This research used qualitative approach because the analysis is in the form of description rather than numeral. Besides, the research was conducted through document analysis as the data were in the form of conversations between two prominent characters in the movie which contain humorous intention. The data were taken from script of the movie.The results of the research shows that 5 out of 7 types of conversational humor were employed in the conversation. Those are teasing (9 data), banter (1 datum), putdown (1 datum), self-denigrating humor (1 datum), retort (2 data), and witticism which only covers 3 out of 8 types under the term namely paradox, irony, and hyperbole which are represented by 2 data of each. In addition, the research also shows that the most predominant function of humor in this movie is as a tool to do power.It is suggested to the next researchers to use natural conversation which is spoken in Bahasa Indonesia as the object under study to test whether the theories used in this study are applicable in context of Bahasa Indonesia or not.